Sensor performance specifications. - Bernstein, D.S (IEEE Control systems magazine)
The author explains sensor specifications which quantify the ability of sensor to provide measurements of physical variables. Sensor manufacturer typically provide information about sensor specifications in the form of a specification sheet. The concepts described will help one interpret the information on a specification sheet. They can be applied to all branches of science and engineering, not just control systems. However, the systems approach of control engineers provides a unique perspective on these topics and associated issues